Dynamical Analysis of a Predator-Prey Model Involving Intraspecific Competition in Predator and Prey Protection - Resmawan, Resmawan; Nuha, Agusyarif Rezka; Nasib, Salmun K.; Nashar, La Ode (Universitas Muhammadiyah Mataram, 2024)
This article explains the interaction of the prey-predator model in the presence of wild harvesting and competition intra-specific predator populations and prey protection zones. Model construction is based on literature studies related to the basic theory of the model and the biological properties between predator and prey populations. This study aims to look at the dynamic conditions of the predator-prey model in the form of the existence of prey and predator populations and the impact that occurs in the long term for both populations due to changes in parameter values. The model analysis begins with the formulation of the solution conditions and boundaries model, and next with the determination of the equilibrium point. Every equilibrium point is analyzed by the characteristic of its stability is neither local or global. The model owns three equilibrium points, namely the equilibrium point of population extinction (E_0), the equilibrium point of predator extinction (E_1), and the equilibrium point of persistence of the two populations (E_2). These equilibrium points are stable locally or globally if certain conditions are met. Next, it is shown that bifurcation proceeds Which describes the changing of characteristic stability point equilibrium Which depends on the threshold parameter values h_1, Ω^*, and ρ^*. In the end, numerical simulations are presented in the form of phase, time-series, and bifurcation diagrams to support the analytical results of the model, as well as to visually show the dynamic behaviour of the interaction between the two populations based on changes in predation levels, illegal harvesting, prey refuge zones, and intra-specific competition.